Peculiarities of language competence forming phases in the 5th form (English after German) - М. М. Прокопчук (Іноземні мови, 2014)
The article deals with the problem of the language competence forming for 5 year students who learn English as the second foreign language after German. The author characterizes the peculiarities of the main stages of the second language competence forming for the young teenager learners.